O estado da arte da interdisciplinaridade: o construto epistemológico de Ivani Fazenda na Pontifícia Universidade Católica de São Paulo (1985 – 2015) - Gentile, Fausto Rogério (2018)
The academic scenario of research on Interdisciplinarity in Brazil, presents at the same time a rupture of values. We see a certain skepticism, an inquiry and indignation about the theoretical-scientific legacy that has been bestowed upon us. Teaching practice and didactics are exposed to a diverse range of models and molds that evidence the exclusion of an intellectual exercise and cherish virtuosity in the management of concepts and techniques, by the immediate need of actors / educators-researchers who do not undertake a dialectic with the theorists of the Sciences of the Education. On the other hand, only the experience and description of practices do not contribute to the construction of efficient indicators capable of showing the development of innovative ways and significant contributions to Education. This research emerges from this scenario, proposing to raise, systematize, organize and discuss the scientific production of Interdisciplinarity held at the Pontifical Catholic University of São Paulo between 1985 and 2015. Using the logic of the State of Art, we present the entire trajectory and production of Ivani Catarina Arantes Farm in relation to Interdisciplinarity. Scientific-historical, aesthetic-critical, this study presents five developmental points. In the first, a brief biography of Fazenda, in the second, a mapping of all her bibliography, in the third, a survey of all dissertations and theses guided by the author, in the fourth, we present the Epistemological Construct of Fazenda and its approximations and digressions with the Science and in the fifth and last Marco, with a conclusion character, we present the legacy of Ivani Fazenda for Interdisciplinarity and for Education in Brazil